Fitur Edukasi Finansial dan Promosi Media Sosial Terhadap Perilaku Investasi Mahasiswa dengan Moderasi Literasi Keuangan - Ni Luh Gede Kusuma Cahaya Ningrum; Made Ratih Nurmalasari (Dharma Ekonomi, 2025)
The development of financial technology (fintech) in the digital era has made it easier for young people, particularly students, to access investment services through applications such as Bibit, Ajaib, Pluang, and Bareksa. The increasing number of young investors has not been fully aligned with the quality of investment decision-making, which is still influenced by low financial literacy, social media promotion, and the availability of financial education features on digital platforms. This study aims to analyze the influence of financial education features and social media promotion on student investment behavior, with financial literacy as a moderating variable. The primary theory used is the Theory of Planned Behavior (Ajzen, 1991), supported by Financial Literacy Theory, Uses and Gratification Theory, and the Technology Acceptance Model. The research method uses a quantitative approach with a population of student users of the Bibit application in Bali. The independent variables in this study include financial education features and social media promotion, while the dependent variable is investment behavior, while financial literacy is positioned as a moderating variable. The results of this study are expected to provide theoretical contributions to the development of management studies, digital marketing, and behavioral finance, as well as practical benefits for investment application developers, educational institutions, and students in fostering rational, intelligent, and sustainable investment behavior in the digital era.